 Quandaries and Queries Hello, I have a problem, like most of your mailers, I do remember BEDMAS but maybe I'm missing the finer points! It's been a while, he goes 4-3(m+1)=(-38) I think this would be at the secondary level. Hope you can help Jamie Hi Jamie, My guess is that you are struggling with the -3. You can think of the left side in two different ways. One way is to see - as subtraction so you want to subtract 3(m+1) from 4. The second way is to see -3 as the number minus three so you want to find minus three times (m+1) and then add it to 4. Using mathematical notation the first intrepretation is 4 - [3(m + 1)] and the second is 4 + (-3)(m + 1) I am going to use the first interpretation, so I want to solve 4 - [3(m + 1)] = - 38 BEDMAS tells me to do brackets (or parentheses) first, so first I see 3(m + 1) = 3m + 3 and hence the problem becomes 4 - [3m + 3] = -38 I want to subtract the entire quantity, 3m + 3, from 4 so this becomes 4 - 3m - 3 = -38 Since 4 - 3 = 1 this is 1 - 3m = -38 I would now add 3m to both sides to get 1 = -38 + 3m Finally add 38 to both sides to get 39 = 3m and thus m = 13. You should now substitute m = 13 into the original expression to verify that this answer is correct. Penny Go to Math Central